The relationship between parenting style and family functioning with preschool children's behavioral problems - Maryam Abbass ghorbani; farima Naghdi (Institute of Management fekrenoandish, 2020)
The aim of the present study was the relationship between parenting style and family functioning with behavioral problems of preschool children. The research method was correlational. The statistical population of this study was all pre-school centers in Qazvin, which were randomly selected from 5 preschool by cluster methods; one class selected randomly from each preschool center, and 20 new students selected randomly from each class 100 althogether. To measure the research variables, the McMaster Family Assessment Test (FAD), the Connors Child Behavioral Problem Scale, and the Bamrind parenting style questionnaire (1937) were used. Simultaneous regression analysis was used to analyze the data. The findings of this study at the significant level of p < 0.05 showed that there was a relationship between parents' parenting style and children's behavioral problems, and also a relationship between parents' parenting style and family function. Also, children's behavioral problems can be predicted by parenting style and family functioning.